Cost Comparison of Drainage Channel Construction Considering Uncertainty of Rainfall Distribution - Intan Supraba; Istiarto Istiarto; Radianta Triatmadja (Journal of the Civil Engineering Forum, 2019)
Rainfall data is the main parameter to design drainage channel. The accuracy of rainfall data determines the accuracy of peak discharge estimation that is used for designing the drainage channel for flood mitigation purpose. The previous study presented that uncertainty of peak discharge is associated with the uncertainty of rainfall distribution and uncertainty of water holding capacity. The main purpose of this study is for understanding the sensitivity of rainfall data by comparing the estimated cost to construct drainage channel based on different values of peak discharges using two different rainfall data set which one rainfall data is created by considering 10% uncertainty of rainfall distribution. This study area is located on Plampang, Sumbawa Besar, West Nusa Tenggara. Results showed that the total cost to construct drainage channel increased by 15% if considering 10% uncertainty of rainfall.